Milites elegantes. Le strutture aristocratiche nel territorio lucchese (800-1100 c.) - TOMEI, PAOLO (Reti Medievali E-Book, 2019)
Lucca occupies a special place in the history and historiography of the early Middle Ages in Italy and Europe. It was the heart of a political body of the Carolingian galaxy, namely the marque of Tuscia, which enjoyed exceptional success and remained vital throughout most of the 11th century. It is also one of the areas most accounted for in sources: the documentation on the Lucca area starting from the beginning of the 8th century is extraordinarily conspicuous and continuous. Hence the choice of this case study, to reflect again on overall historical transformations. This book starts from a systematic research on the documentary sources of Lucca, so wide that they are still largely unexplored, and aims at reconstructing the fundamental parameters that governed the functioning of a court society, and at following its transformation processes up to the noble and chivalric age. At the centre of the investigation lies the social segment which gradually assumed aristocratic features and a more defined profile of distinction, and promoted the foundation of castles in the countryside as well as the formation of territorial areas on which to exercise powers of command and coercion.